(untitled) (Bulletin KNOB, 2013)
Between 1920 and 1940, the engineer A.L.W.E. van der Veen (PhD) was involved in many restorations as a consultant on natural stone, at first under the authority of the National Bureau for Monuments and later as an independent consultant. After his studies in mining engineering at the former Technische Hoogeschool Delft, where he wrote his doctoral thesis on the symmetry of diamond, he became involved with monuments and their preservation. Van der Veen’s geological expertise enabled him to determine the nature and origin of natural stone used in historical buildings and advise on suitable replacement material. The article at hand provides an overview of Van der Veen’s life and describes his introduction into the world of monuments preservation. It also describes in more depth the advice he gave with regard to types of natural stone that was historically often applied in the Netherlands, such as sandstone, white Belgian sandy limestone, and tuff. His efforts to provide advice that was in accordance with the principles of restoration as articulated in 1917 are illustrated by his reasoning in choosing replacement stone. His advice on choosing limestone from France and tuff from the German Eifel constitutes the main body of the article at hand. It shows that his advice sometimes lacked foundation or differed from earlier advice. Nevertheless, Van der Veen has had a profound influence on the choice of replacement stone. Gaining insight in his reasoning is therefore important, as it is an aspect that needs to be considered in the assessment of restoration interventions, for instance when new restorations make it necessary to replace stone that was used in previous restorations.